Perencanaan Struktur Bangunan Industri Pengolahan Kedelai pada Pabrik Tahu di Kecamatan Kaliwates, Kabupaten Jember - firdaus firmansyah; Senki Desta Galuh; Arief Alihudien (Jurnal Rekayasa Infrastruktur HEXAGON, 2026)
This study aims to design the structure of a Wastewater Treatment Plant (WWTP) for the soybean processing industry in Kaliwates Subdistrict, Jember Regency, as an effort to reduce environmental pollution caused by liquid waste from tofu production. The research stages included collecting production data, measuring wastewater flow rates, analyzing wastewater characteristics based on pH, BOD, COD, and TSS parameters, and conducting soil mechanics analysis to determine soil bearing capacity as the basis for WWTP structural design. The results of the observations showed that the wastewater generated is still discharged directly into the environment without treatment, thereby potentially degrading water body quality. The measured wastewater flow rate was 0.4372 m³/day, with BOD and COD levels exceeding established quality standards. Therefore, a wastewater treatment system combining anaerobic biofilters, aerobic biofilters, and a constructed wetland was planned, as this combination is considered effective for reducing pollutant levels. Furthermore, geotechnical analysis results indicate that the soil at the study site has adequate bearing capacity with a safety factor of 3.11, making it safe to support the planned wastewater treatment plant structure. This design is expected to serve as an effective, economical, and sustainable wastewater treatment alternative for small- and medium-scale tofu industries.